Gender Equality and Positive Action: Evidence from UK Universities - Danula K. Gamage; Almudena Sevilla (Institute of Labor Economics (IZA), 2019)
This paper examines the impact of the Athena Scientific Women's Academic Network (SWAN) Charter on the wages and employment trajectories of female faculty. The Athena SWAN Charter is a gender equality initiative that formally recognises good practice towards the representation and career progression of women in Science, Technology, Engineer, Mathematics, and Medicine (STEMM) through an accreditation process. We find that the gender wage gap closes after Athena SWAN accreditation. However, female faculty at the non-professorial level are not more likely to being promoted to professor after accreditation, or to move to an Athena SWAN accredited university. Taken together these results suggest that the higher wage growth experienced by female non-professorial faculty after Athena SWAN accreditation is likely to come from pay rises within a particular rank.
Keywords: I23; J16; J31; J44; 330; gender equality; positive action; gender pay gap; Athena SWAN